Analisis nilai nilai pancasila fundamental dan implementasi di indonesia - Rozi, M Fakhrur (Maliki Interdisciplinary Journal, 2025)
Pancasila juridically and philosophically is a Grundnorm and a national ideology that functions to unite diversity and become the foundation of law in Indonesia. However, contemporary reality shows that there is a normative gap between ideal values and empirical practice. External challenges such as globalization and transnational ideology, as well as internal problems in the form of political polarization and economic disparities, cause the value of Pancasila to be internalized to the maximum. The existing character education efforts so far are considered insufficient to ensure the ideological resilience of the community. This research aims to identify the fundamental values of Pancasila through ontological, epistemological, and axiological approaches, and examine their implementation in the political, legal, and social sectors. The study also maps the challenges and opportunities in the modern era to formulate strategic policy recommendations. Through this analysis, the research emphasizes the urgency of reorienting Pancasila not just as a symbol, but as an ethical paradigm and praxis guidelines that are relevant in solving the nation’s multidimensional challenges.